Prospects on bio-based 2,3-butanediol and acetoin production: recent progress and advances - Maina, Sofia; Prabhu, Ashish A.; Vivek, Narisetty; Vlysidis, Anestis; Koutinas, Apostolis; Kumar, Vinod (Elsevier, 2021)
The bio-based platform chemicals 2,3-butanediol (BDO) and acetoin have various applications in chemical, cosmetics, food, agriculture, and pharmaceutical industries, whereas the derivatives of BDO could be used as fuel additives, polymer and synthetic rubber production. This review summarizes the novel technological developments in adapting genetic and metabolic engineering strategies for selection and construction of chassis strains for BDO and acetoin production. The valorization of renewable feedstocks and bioprocess development for the upstream and downstream stages of bio-based BDO and acetoin production are discussed. The techno-economic aspects evaluating the viability and industrial potential of bio-based BDO production are presented. The commercialization of bio-based BDO and acetoin production requires the utilization of crude renewable resources, the chassis strains with high fermentation production efficiencies and development of sustainable purification or conversion technologies.
Keywords: 2,3-Butanediol; Acetoin; Metabolic engineering; Bioprocess development; Downstream processing; Techno-economic evaluation; Platform chemicals